Physico-Microbial Properties of Cervico-Vaginal Mucus and its Antibiotic Sensitivity Pattern in Repeat Breeding Buffaloes - SHARMA, SHIV KUMAR; SHARMA, HITENDRA; DHAMI, A J; BHONG, C D (The Indian Journal of Animal Reproduction, 2023)
Forty five cervico-vaginal mucus samples from repeat breeding buffaloes on examination revealedclear thin watery, clear stringy and turbid consistency of mucus in 55.55, 33.33 and 11.11 % cases,respectively; while as in IO normal cyclic animals, 70.00 and 30.00 % samples were clear stringy and clearthin watery, respectively. Typical, atypical and nil fern pattern of oestrual mucus was observed in 33.33,60.00 and 6.66 % samples of repeat breeders, and in 80, 20 and 0.00 % of normal cyclic buffaloes,respectively. Maximum number of normal cyclic and repeat breeding buffaloes conceived when they hadclear stringy mucus (85.72 and 60.00 %), followed by those with clear thin watery mucus (33.33 and 20.00%) and those with typical fern pattern (87 .50 and 46.66 %), but none with turbid mi.Jc us and nil fernpattern. The spinnbarkeit value of mucus from repeat breeding and normal cyclic buffaloes was ide.ntical(9.76 ± 0.56 and I 0.30 ± 0.93 cm), but those conceived had significantly higher (P
Keywords: Cervico-vaginal mucus; Physical properties; Microbial isolates; Drug Sensitivity; Repeat breeding; Buffaloes